2012
DOI: 10.1245/s10434-012-2726-3
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Survival after Lung Metastasectomy in Colorectal Cancer Patients: A Systematic Review and Meta-Analysis

Abstract: Clinical variables associated with prolonged survival after surgery for LM in CRC patients include prolonged disease-free interval between primary tumor and metastatic spread, normal prethoracotomy carcinoembryonic antigen, absence of thoracic node involvement, and a single pulmonary lesion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

13
254
1
11

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 355 publications
(279 citation statements)
references
References 33 publications
13
254
1
11
Order By: Relevance
“…Conversely, the presence of synchronous or metachronous resected liver metastases was not significantly related to poor survival (7).…”
Section: Introductionmentioning
confidence: 78%
See 2 more Smart Citations
“…Conversely, the presence of synchronous or metachronous resected liver metastases was not significantly related to poor survival (7).…”
Section: Introductionmentioning
confidence: 78%
“…Nevertheless, disappointing results after chemotherapy in patients with advanced CRC, laid solid foundations for pulmonary resection of lung metastases (4,5). In fact, pulmonary metastasectomy is being commonly performed worldwide in selected patients with reported 5-year survival data ranging from 27% to 68% (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Surgical resection of both metastatic and locally recurrent disease is now widely practiced with a good proportion of patients enjoying long-term survival. [9][10][11] These meta-analyses report prognostic features for survival following recurrence; however, they include patients with both synchronous and non-synchronous presentations and the disease biology may be different. Furthermore, the prognostic factors identified typically relate to observations at the time advanced disease is identified, such as number and size of metastatic lesions, and carcinoembryonic (CEA) antigen level, 10,11 with less emphasis placed on characteristics of the primary tumor.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason it is wise to conclude that the less invasive approach should be used, until proved differently. Furthermore another review reported that prolonged long term survival in LM of colorectal cancer is obtainable only in patients with single metastasis (17). Although some authors first reported that repeated metastasectomy could prolong survival, successively reviewing again the data they think that better survival attributed to LM may be due to the selection of patients who are innately destined to live longer (18,19).…”
mentioning
confidence: 99%